2016
DOI: 10.1063/1.4943896
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid Rayleigh-Taylor-current-driven coupled instability in a magnetohydrodynamically collimated cylindrical plasma with lateral gravity

Abstract: We present an MHD theory of Rayleigh-Taylor instability on the surface of a magnetically confined cylindrical plasma flux rope in a lateral external gravity field. The Rayleigh-Taylor instability is found to couple to the classic current-driven instability, resulting in a new type of hybrid instability that cannot be described by either of the two instabilities alone. The lateral gravity breaks the axisymmetry of the system and couples all azimuthal modes together. The coupled instability, produced by combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…These effects become important at small length scales such as the ion Larmor radius or the ion skin depth where MHD is no longer valid. For example, in a recent set of experiments involving a plasma jet, 7,10 a kinkinduced Rayleigh-Taylor instability 11 effectively narrowed the plasma column to the ion skin depth scale, transitioning from an MHD-governed system to a system governed by Hall and electron inertia effects. A strong suggestion that Hall and electron inertia terms were important was the observed emission of circularly polarized whistler waves in association with the reconnection.…”
Section: Introductionmentioning
confidence: 99%
“…These effects become important at small length scales such as the ion Larmor radius or the ion skin depth where MHD is no longer valid. For example, in a recent set of experiments involving a plasma jet, 7,10 a kinkinduced Rayleigh-Taylor instability 11 effectively narrowed the plasma column to the ion skin depth scale, transitioning from an MHD-governed system to a system governed by Hall and electron inertia effects. A strong suggestion that Hall and electron inertia terms were important was the observed emission of circularly polarized whistler waves in association with the reconnection.…”
Section: Introductionmentioning
confidence: 99%
“…Their analysis showed that though these physics do not alter the threshold for instability, the ion-neutral collisions can vastly reduce the growth rate of the instability. Zhai & Bellan (2016) developed a model of a hybrid of the current-driven kink instability and the magnetic Rayleigh-Taylor instability in a flux tube to model the experimental findings of Moser & Bellan (2012), where they found this new geometry was able to explain the growth of the observed instability. For a detail investigation into many of the important process relating to the RayleighTaylor instability including the extension to stratified atmospheres, compressibility, inhomogeneity and continua see, for example, Goedbloed & Poedts (2004) and Goedbloed et al (2010).…”
Section: The Rayleigh-taylor Instability In Astrophysical Plasmamentioning
confidence: 99%
“…In a similar process to that seen in Isobe et al (2006), the nonlinear development led to magnetic reconnection. Zhai and Bellan (2016) developed linear theory to describe the growth of the hybrid of the current driven kink instability and the gravitationally driven magnetic Rayleigh-Taylor instability. They found that the combined instability grew significantly faster than either of the two individual instabilities by themselves.…”
Section: Plasma and Fluid Experimentsmentioning
confidence: 99%